Effects of various virulent strains of Agrobacterium tumefaciens on genetic transformation of banana (Musa sp.) cultivar williams - Esuola, C.O.; Tripathi, L.; Fawole, I. (2011)
Investigations were conducted to select the appropriate Agrobacterium tumefaciens strains for efficient transformation of the banana cultivar ‘Williams’. Three A. tumefaciens strains (EHA105, C58, and GV2260) were used for the study. The ability of these strains to transfer β-glucuronidase (GUS) gene into banana tissues was assessed through GUS histochemical assay. Results obtained demonstrated that GUS activity was more enhanced in banana meristem pieces that were co-cultivated with EHA105 strain than in tissues that were co-cultivated with the other two strains. The least transient GUS expression was recorded in banana tissues that were co-cultivated with C58. The effect of the strains on efficient regeneration also indicated that EHA105 is more efficient than the other two strains. Therefore, Agrobacterium tumefaciens strain EHA105 appears to be the appropriate strain for efficient transformation of banana.